Brief notes on the subject or social agent in three currents of sociological thought - Mora, Maynor Antonio (2021)
This essay analyzes, in a very brief and general way, three currents of sociological theory and social philosophy (hermeneutic-constructivist currents, so-called critical currents, and poststructuralist structuralism). The theoretical approach iscarried out from the point of view of the agent or social subject. The essay is didactic, comparative and preliminary in nature regarding future investigations of the subject.